Analisis Faktor Risiko pada Saham Perbankan ASEAN – 4 Periode 2006 – 2015 Dengan Pendekatan Fama and French Three Factor Model dan Intertemporal Capital Asset Pricing Model - Adela, Lita Tiami; Husodo, Zaafri Ananto (Jurnal Manajemen dan Usahawan Indonesia, 2020)
This research aims to determine the effect of market, size, and value on Fama and French Three Factor Model toward portofolio excess return using value weighted and equally weighted method on ASEAN – 4 banking stock. This research also determine the effect of market factor and term struc- tured factor on Intertemporal Capital Asset Pricing Model on ASEAN – 4 banking stock. The result shows only market factor that has significant effect towards banking stock portofolio excess return on Fama and French Three Factor Model, using both value weighted dan equally weighted. The term- structure factor on Intertemporal Capital Asset Pricing Model has significant effect towards banking stock portofolio excess return using equally weighted method.